Role of Accounting Information Systems in Selected Small Businesses and the Reliability Level of Financial Reporting - Blau Somaliland - Chikati, David Kavinje (Journal of Global Economy, Business and Finance, 2025)
Purpose: This study to determine the correlation between the role of accounting information system and reliability financial reporting in small businesses of Burao district, Somaliland. Methodology: The study adopted descriptive research design, specifically cross - sectional survey design using both the quantitative and qualitative methods of data collection. Descriptive study according to Gall et al (1996) enables the researcher to collect information from a cross section of a given population. This study design was used because it is the most used research method in social research, the target Population included a total of 50 participants from the owners and managers of the small and medium businesses of Burao downtown. Respondents were grouped into strata's consisting of the top level, functional level and operational level and purposive sampling was conducted in each stratum to get relevant information for the study without any bias. Primary data was collected with questionnaires and in - depth interviews. Considering the nature of the data that was collected, it will be very appropriate to use Both quantitative and qualitative approaches to analyze the data. To analyze the data it was used SPSS, graphs and excel methods. Findings: The finding of this study in small businesses, accounting information systems play a critical role in financial management. These systems provide small business owners with the ability to track finances, monitor expenses, and make informed decisions about the business's future. Conclusion: Accounting information systems play a crucial role in small businesses as they enable them to manage their finances effectively. By providing accurate financial data, enabling financial analysis, and forecasting, and facilitating tax compliance, accounting information systems help small businesses make informed decisions and achieve their financial goals.